A spatial transcriptomic signature of 26 genes resolved at single-cell resolution characterizes high-risk gastric cancer precursors - Robert J. Huang; Ignacio A. Wichmann; Andrew Su; Anuja Sathe; Miranda V. Shum; Susan M. Grimes; Rithika Meka; Alison Almeda; Xiangqi Bai; Jeanne Shen; Quan Nguyen; Ingrid Luo; et al. (npj Precision Oncology)
Abstract Gastric cancer precursors demonstrate highly-variable rates of progression toward neoplasia. Certain high-risk precursors, such as gastric intestinal metaplasia with advanced histologic features, may be at up to 30-fold increased risk for progression compared to lower-risk intestinal metaplasia. The biological differences between high- and low-risk lesions have been incompletely explored. In this study, we use several clinical cohorts to characterize the microenvironment of advanced gastric cancer precursors relative to low-risk lesions using bulk, spatial, and single-cell gene expression assays. We identified a 26-gene panel which is associated with advanced lesions, localizes to metaplastic glands on histopathology, and is expressed in aberrant mature and immature intestinal cells not normally present in the healthy stomach. This gene expression signature suggests an important role of the immature intestinal lineages in promoting carcinogenesis in the metaplastic microenvironment. These findings may help to inform future biomarker development and strategies of gastric cancer prevention.